An experimental approach to the calculate of air-to-water dose ratio in Tehran Research Reactor (TRR) spent fuel using TL dosimeter - R. Adeli (Nuclear Engineering and Technology)
The Tehran Research Reactor (TRR) is a reliable neutron source in Iran. Dealing with the spent fuel (SF) is one of the most challenging issues in the peaceful use of nuclear technology, both in protecting the public and the environment from the hazardous effects of ionization radiation.In this experimental research work the GR-200 as a thermoluminescence-dosimeter (TLD) was used for measuring the dose rate of this high dose rate item in water and air environments. To overcome the challenge of air dose assessment, a waterproof polymer tube was designed and placed in front of a low burn-up SF. Also, a thick stainless steel slab was fabricated to both immerse the dry channel in water and prevent the TLD saturation. The distances of 20, 50 and 100 cm were considered to measure the dose rate in the air and the distances of 10, 20 and 50 cm were chosen to measure the dose rate in the water environment. Accordingly, the air-to-water dose rate ratio (100 cm of air and 20 cm of water) is 0.11. The obtained dose rate ratios matrix at different distances in these two environments will enable us to measure the dose rate in water and then calculate the dose rate in air without any direct measurement.